CONSTRUCTIVE WAYS IN TEACHING PEDAGOGICAL TERMINOLOGY - Mavlonova Mohira Umirbek qizi (American Journals, 2023)
The article discusses effective ways to teach pedagogical terms. It also helps students to practice with pedagogical terms, while such activities help them to strengthen their vocabulary and develop their lexical skills. The following article can be formulated as the necessity to maintain professional information while listening to or reading academic works, and the need to use pedagogical terms in oral and written communication to urge the students to master the terminology.
Keywords: pedagogical, terminology, method, interactive, teaching process, foreign language, lexical competence